Borax promotes the facile formation of hollow structure in Cu single crystalline nanoparticles for multifunctional electrocatalysis. Issue 4 (7th March 2019) - Jia, Baorui; Zhao, Yongzhi; Zhang, Zili; Liu, Luan; Qin, Mingli; Wu, Haoyang; Liu, Ye; Qu, Xuanhui; Qi, Genggeng
Abstract : Hollow Cu2 O and Cu are efficiently prepared using borax as structure-directing agent for electrocatalysis of glucose oxidation and H2 O2 reduction. Abstract : Hollow nanostructured materials have numerous applications in various fields, such as electrochemical energy storage and electrocatalysis. These materials are commonly synthesized by template-based techniques. However, many templating methods are known to be time-consuming, laborious, and unsuitable for large-scale production. Here, for the first time, we find that borax can efficiently promote the formation of hollow metal oxide and metal in solution. The key role of borax is recognized as a structure-directing agent, different from the reported hard templating or Ostwald ripening. We prepared hollow Cu2 O nanospheres and Cu2 O coated hollow Cu single crystals (Cu/Cu2 O) under different reduction conditions by this scalable template-free method. The hollow structure improves the density of active sites per unit mass, meanwhile the well-defined Cu/Cu2 O heterojunction with a single-crystalline Cu core facilitates electron transfer. Therefore, the Cu/Cu2 O shows excellent electrocatalytic activities for glucose oxidation and hydrogen peroxide reduction. The as-fabricated nonenzymatic sensor has an ultrawide linear measurement range (up to 14 mM glucose) and high detection sensitivity for glucose (453 μA cm −2 mM −1 ) and hydrogen peroxide (2.55 μA cm −2 mM −1 ).